Utilization of Antenatal Services among Postnatal Mothers - Gautam Bhattarai, Saraswoti Kumari; Pahadi, Nirmala; Chaulagain, Sandhya; Mahat, Shrijana; Pantha, Asha; Khadka, Rabin (Journal of Nepal Health Research Council, 2023)
Background: Antenatal care is medical supervision and care given to pregnant women to ensure, support and maintain maternal and fetal well-being throughout the pregnancy. Therefore, this study was done to find out the utilization of antenatal services among postnatal mothers. Methods: The descriptive cross sectional study design was used to identify the utilization of antenatal services among postnatal mothers who came in Maternal and Child Health Clinic for the immunization of baby. Total 367 postnatal mothers within one year of childbirth were recruited by simple random sampling technique, and data was collected with face-to-face interview by using semi structured interview schedule. Analysis was done by using descriptive and inferential statistics. Results: All postnatal mothers consumed iron and folic acid during pregnancy, 96.2% consumed until the childbirth, 94.0% got freely, 97.0% taken anti helminths drug, 98.1% did urine test, 98.1% did blood test, 97.8% got ultrasound service, and 96.5% received Td vaccine. Likewise, higher proportion had checked weight 98.6% and lower proportion had checked height 86.9%. Similarly, majority 90.2% received counselling on danger signs and only 26.2% received the counselling on preparation of items safe delivery and care of newborns. There is significant association of antenatal care service utilization with postnatal mothers’ educational level and her husband’s occupation (P<0.05 level). Conclusions: Although most of the postnatal mothers utilized antenatal care services, some aspect of antenatal education and counselling need to be improved such as preparation of item for delivery and new born care, finance, and blood donors. Keywords: Antenatal care; antenatal care utilization; satisfaction.